2019
DOI: 10.1002/jcb.29269
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin induced by Treponema pallidum predicted membrane protein Tp0965 mediates the activation of endothelial cell via MAPK signaling pathway

Abstract: Chemerin, a chemoattractant protein, is involved in endothelial dysfunction and vascular inflammation in pathological conditions. In a recent study, we observed the upregulation of chemerin in endothelial cells following in vitro treatment with Treponema pallidum. Here, we investigated the role of chemerin in endothelial cells activation induced by the T. pallidum predicted membrane protein Tp0965. Following stimulation of human umbilical vein endothelial cells (HUVECs) with Tp0965, chemerin and its receptor c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It is emphasized that the inflammatory response is responsible for syphilis pathogenesis during the invasion and persistence of T. pallidum. By recruiting immune cells to sites of tissue damage, vasculitis invokes and ultimately leads to T. pallidum dissemination by destroying the endothelial barrier, dependent on the activation of the RhoA/ROCK and MAPK signaling pathways (Zhang et al 2019). Our previous studies found that recombinant Treponema pallidum protein 17 (rTp 17) increased the expression of the gene encoding monocyte chemoattractant protein-1 (MCP-1) in HUVECs (Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that the inflammatory response is responsible for syphilis pathogenesis during the invasion and persistence of T. pallidum. By recruiting immune cells to sites of tissue damage, vasculitis invokes and ultimately leads to T. pallidum dissemination by destroying the endothelial barrier, dependent on the activation of the RhoA/ROCK and MAPK signaling pathways (Zhang et al 2019). Our previous studies found that recombinant Treponema pallidum protein 17 (rTp 17) increased the expression of the gene encoding monocyte chemoattractant protein-1 (MCP-1) in HUVECs (Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The DCs then produce type I interferons, leading to proinflammatory polarization of adipose tissue-resident macrophages [194]. Monocyte-derived macrophages also express CMKLR1, and chemerin similarly promotes macrophage migration [195,196]. Herova et al determined that CMKLR1 is only expressed on M1 macrophages, but not M2 macrophages, indicating that the receptor is involved in recruitment of M1 macrophages to inflamed tissues [197].…”
Section: Chemerin and Immune Functionmentioning
confidence: 99%
“…Tp0965 can stimulate the expression mRNA and protein of ICAM‐1, E‐selectin, and monocyte chemotactic protein‐1 (MCP‐1) of HUVEC, and decrease the Claudin‐1 expression level of the tight junction protein, leading to increased vascular endothelial cell permeability, which further assists T. pallidum in crossing the vascular endothelium 22 . Recent research results have highlighted that Tp0965 induced Chemerin in endothelial cell dysfunction, which may be involved in the immune pathogenesis of vascular inflammation of syphilis 27 …”
Section: Direct Effects Of T Pallidum To Endothelial Cellsmentioning
confidence: 99%
“… 22 Recent research results have highlighted that Tp0965 induced Chemerin in endothelial cell dysfunction, which may be involved in the immune pathogenesis of vascular inflammation of syphilis. 27 …”
Section: Direct Effects Of T Pallidum To Endotheli...mentioning
confidence: 99%